PENGEMBANGAN JIWA EDUPRENEURSHIP SISWA MELALUI KEPEMIMPINAN YANG DEMOKRATIS DI SEKOLAH - Zakaria Zakaria; Ganefri Ganefri; Asmar Yulastri (LP2M Universitas Bina Bangsa, 2022)
In our country we face several important and crucial issues regarding poverty. One of them is to overcome unemployment. One thing that needs to be increased is the number of entrepreneurs must be increased. So, the purpose of this writing is to describe the development of the edupreneurship spirit through democratic leadership in educational institutions and to foster an entrepreneurial spirit in students. This study uses a qualitative approach with a literature study method by reviewing books and journals. The formulation of the problem in this research is how to develop the spirit of edupreneurship through democratic leadership in educational institutions. This study uses a qualitative approach with a background in edupreneurship and democratic leadership in educational institutions. The results of the discussion state that (1) the development of the edupreneurship spirit and democratic leadership, where students are instilled the edupreneurship spirit so that they can be entrepreneurs and can create businesses and open job vacancies taught by facilitators such as school principals, teachers who have a democratic leadership spirit (2 ) fostering the spirit of edupreneurship through the teaching factory, where this activity receives orders, analyzes, states readiness to work on orders, quality control, and submits orders, which can foster significant edupreneurship and entrepreneurial spirit, confidence, dare to take risks (3) foster edupreneurship spirit through the bussines center, where business practices use market observations, place orders or purchases from the bussines center